A Genotyping Study in Benin Comparing the Carriage of Plasmodium falciparum Infections Before Pregnancy and in Early Pregnancy: Story of a Persistent Infection. (22nd June 2020) - Jafari-Guemouri, Sayeh; Courtois, Laura; Mama, Atika; Rouas, Baptiste; Neto Braga, Gabriel; Accrombessi, Manfred; Massougbodji, Achille; Ding, Xavier C; Tuikue Ndam, Nicaise; Fievet, Nadine; Briand, Valérie
Abstract: Background: Malaria infections in the first trimester of pregnancy are frequent and deleterious for both mother and child health. To investigate if these early infections are newly acquired or already present in the host, we assessed whether parasites detected before pregnancy and those detected in early pregnancy are the same infection. Methods: We used data from the preconceptional "RECIPAL" study (Benin, 2014–2017). Sixty-three pregnant women of 411 included who had a malaria infection detected by quantitative polymerase chain reaction both before pregnancy and at the first antenatal care (ANC) visit were selected for this study. Two highly polymorphic markers, msp-2 and glurp, and a fragment-analysis method were used to enumerate the Plasmodium falciparum genotypes and to quantify their proportions within isolates. An infection was considered as persistent when identical msp-2 and glurp genotypes were found in the corresponding prepregnancy and early-pregnancy samples. Results: The median time between the 2 malaria screenings was 3 months. The median gestational age at the first ANC visit was 6.4 weeks. Most infections before pregnancy were submicroscopic infections. Based on both msp-2 and glurp genotyping, the infection was similar before and in early pregnancy in 46% (29/63) of cases. Conclusions: Almost half of P. falciparum infections detected in the first trimester originate before pregnancy. Protecting young women from malaria infection before pregnancy might reduce the prevalence of malaria in early pregnancy and its related poor maternal and birth outcomes. Abstract : To distinguish between new and persistent malaria infection in early pregnancy, we enumerated and compared Plasmodium falciparum genotypes in isolates both before and in the first weeks of pregnancy. Persistent infections from preconception accounted for half the cases.